Blood Diamonds in the World Economy - Pospíšil, Kristián; Štěrbová, Ludmila, 1957-; Halík, Jaroslav, 1961-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The principal objective of this thesis shall be to map and delineate the realities connected with the exploitation, processing, and trade with diamonds. Most importantly, it revolves around the pivotal issue of trade with the so-called blood or conflict diamonds. Numerous measures have been taken to curb trade with the conflict diamonds, namely the Kimberley Process Certification Scheme established by the UN General Assembly, which unites administrations, civil societies and industry with the aim to reduce the flow of “rough diamonds used to finance wars against governments” around the world. In essence, it shall ensure that conflict diamonds do not enter the mainstream rough diamond market. The system, however, has been criticized for having so many loopholes and being so vaguely defined that it fails in its purpose to assure that a particular diamond is “conflict-free.” The thesis is divided into 4 chapters. The first one describes diamonds as minerals and explains their unique properties, which make them invaluable for the industry and as pieces of jewellery. The second chapter introduces conflicts that took place in diamond-exporting countries in recent history but prior to the establishment of the KP. Some countries like Sierra Leone or Angola became war zones others have been fertile ground for other human rights violations or smuggling. The third chapter will take a closer look at the measures that were taken since those incidents. Special attention shall be devoted to the wording of the Kimberley Process Certification Scheme as it has been under criticism for its ineffectiveness, while the following subchapters shall deal with the involvement of the NGOs and the legal aspects of the human rights violations, along with enforcement proceedings or lack thereof.
In the final chapter, we examine how is trade regulated by individual governments of countries, where the trade with blood diamonds flourishes and compare them with those, which have been capable of curtailing the practices. The conclusion summarises our findings and recommendations against illicit trade with conflict diamonds.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses